2006
DOI: 10.1080/08880010500313272
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bone Mineral Density at Different Phases of Therapy of Childhood All

Abstract: In the present study the authors evaluated the status of spinal bone mineral density (BMD) using dual-energy X-ray absorptiometry in a group of 31 children with acute lymphoblastic leukemia, treated by ALL-BFM protocols without irradiation, at different phases of their treatment. These patients were studied (1) within 2 months of diagnosis (group 1, n = 17, median time postdiagnosis 17 days), (2) during chemotherapy (group 2, n = 16, median time on treatment 22 months), and (3) shortly after completion of ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
1
15
0
1
Order By: Relevance
“…Rates of osteoporosis were 17%, 25%, and 50% in groups 1, 2, and 3, respectively, suggesting that osteoporosis rate increased with time, reaching the highest values by the end of treatment. Most of these studies [18,21] investigated bone health parameters at different stages of treatment, although some studies compared data obtained at diagnosis with those obtained at only 6th month of treatment [22]. The results of the present study are supported by a limited number of studies that investigated BMD at various time points after completion of treatment in a group of patients similar to our study population [7].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Rates of osteoporosis were 17%, 25%, and 50% in groups 1, 2, and 3, respectively, suggesting that osteoporosis rate increased with time, reaching the highest values by the end of treatment. Most of these studies [18,21] investigated bone health parameters at different stages of treatment, although some studies compared data obtained at diagnosis with those obtained at only 6th month of treatment [22]. The results of the present study are supported by a limited number of studies that investigated BMD at various time points after completion of treatment in a group of patients similar to our study population [7].…”
Section: Discussionsupporting
confidence: 66%
“…Arikoski et al [22] found significant decreases in BMD evaluated by DEXA in children with cancer (15 with leukemia, 12 with lymphoma, and 19 with solid tumors) 6 months after diagnosis, although they did not detect any difference between groups with regard to BMD z-scores either at diagnosis or 6 months later. Maniadaki et al [18] reported BMD zscores in children with acute lymphoblastic leukemia (ALL) as −0.74 ± 0.32, −1.59 ± 0.24, and −2.03 ± 0.27 at onset (group 1), in the course of (group 2), and at completion (group 3) of CT, respectively, and found statistically significant differences between groups 1 and 3. Rates of osteoporosis were 17%, 25%, and 50% in groups 1, 2, and 3, respectively, suggesting that osteoporosis rate increased with time, reaching the highest values by the end of treatment.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Low bone mineral density [15], loss of lean muscle mass [6,7], motor neuropathy [810], muscle weakness [7] and impaired fitness [1115] are possible during and after therapy, and have been attributed to both leukemia and its treatment. Even though correlations between acute impairment and long-term functional loss have not been evaluated, early initiation of exercise or physical activity interventions have been proposed to restore function or to prevent impairments for children with newly diagnosed ALL [1,1618].…”
Section: Introductionmentioning
confidence: 99%
“…Previous dual-energy x-ray absorptiometry (DXA)-based studies documented bone deficits in childhood ALL (13)(14)(15)(16)(17). However, DXA is a two-dimensional projection technique that does not provide discrete measures of trabecular and cortical bone.…”
mentioning
confidence: 98%